2015
DOI: 10.2116/analsci.31.1041
|View full text |Cite
|
Sign up to set email alerts
|

Label-free Detection of Zn2+ Based on G-quadruplex

Abstract: Herein, we developed a sensing strategy for the label-free detection of Zn 2+ based on G-quadruplex. In the absence of Zn 2+ , there was a fluorescence enhancement of thioflavin T by interaction with human telomere sequence. On the addition of Zn 2+ , Zn 2+ induced a more compact G-quadruplex structure to release thioflavin T, resulting in a fluorescence decrease. This simple "mix-then-detect" method gave the detection limit of 0.91 μM with linear dynamic ranges from 0 to 10 μM. Because it does not require the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…ThT is a hydrophilic dye and gives strong fluorescence enhancement upon binding to G-quartet motifs. 65,66,69 It was found that an aqueous alkaline solution of ThT (5 mM) showed negligible fluorescence (Fig. S4a, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…ThT is a hydrophilic dye and gives strong fluorescence enhancement upon binding to G-quartet motifs. 65,66,69 It was found that an aqueous alkaline solution of ThT (5 mM) showed negligible fluorescence (Fig. S4a, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…75 G4s have been widely used as signal transducers in sensing applications by employing G4-binding fluorescent ligands or dyes. 76,77 Our group has devoted continuous efforts towards the development of LFBs using G4-specific dyes for the sensing of ions, 81,82 nucleic acids, 83,84 protein and enzyme activity [85][86][87] etc. As shown in Fig.…”
Section: Lfbs Based On G4-specific Dyesmentioning
confidence: 99%
“…The spectrophotometric method is a well-developed, low cost, versatile and simple analytical technique, which had been widely applied in detecting some metal ions, 22,23 proteins, 24,25 carbon dots 26,27 and organic compounds. 28 Nowadays, there are several studies on AO detection, 6,7,29 but in this work, we have, for the first time, introduced BSA for highly selective and sensitive determination of AO by fluorescence.…”
Section: Introductionmentioning
confidence: 99%